Infrared Non‐Invasive Exhaled Biomarker Sensing: A Review - Uthra B; Ranu; Md. Ataur Rahman; Sharath Sriram; Pankaj B. Agarwal (Advanced Sensor Research, 2024)
Abstract Exhaled breath analysis is considered an effective tool for diagnosing the patient's metabolic status because of its non‐invasive nature. Gas chromatography‐mass spectrometry (GC‐MS) and other mass spectrometry techniques are widely used for exhaled breath analysis. Nevertheless, the requirement of a handheld device for real‐time analysis and rapid processing time of multiple samples leads to advancing infrared (IR) based breath gas sensing techniques. Herein, the IR gas sensing technologies are discussed with a focus on non‐dispersive infrared (NDIR), photoacoustic (PAS), and tunable diode laser absorption spectroscopy (TDLAS) gas sensing technologies because of their highly selective gas detection among compound gases (mixture of VOCs), as well as their corresponding sensing mechanisms and characteristics, for real‐time monitoring of exhaled biomarkers. Carbon dioxide, acetone, ammonia, nitric oxide, methane, and ethylene are the significant biomarkers elaborated in this work with their respective clinical applications and the significance of non‐invasive real‐time monitoring using IR detectors. Challenges in selectivity and clinical trials leads to focus on this review. Current market analysis, present status of different techniques to detect specific biomarkers and other challenges with their possible solutions discussed in this review aid in developing highly selective IR‐based handheld breath VOC analyzers for early diagnosis and screening.